Tomada de decisão no design de interiores face às influências da oferta de materiais favoráveis à sustentabilidade - Talissa Bedran Linhares (2020)
This research aims to analyze the interrelation between the reality of Materiais Favoráveis à Sustentabilidade (MFS - Sustainability Favoring Materials)’s offer in stores and from salespeople with the decision making of professionals working in the interior design market in Belo Horizonte - MG. For this, through a quantitative and qualitative approach, information from local material suppliers was evaluated, in addition to the interior design professionals working in the local sphere, adopting an intentional non-probabilistic sampling. The intersection between the professionals that were approached, from different areas, demonstrated the perception of different actors involved in interior projects, highlighting the importance of interdisciplinarity and the awareness of all spheres involved in the adoption of MFS. When analyzing the results, it was evidenced that none of the researched materials has Type I certifications, which assesses the entire life cycle of the material. Thus, the study found that no material evaluated can be classified as MFS. Even so, there are initiatives that can be favorable to sustainability, such as: sustainable forest management; limiting the amount of chemicals harmful to the environment; environmental and social education actions; use of recycled raw material and production processes that reuse various types of waste. These materials, which met some of the criteria, even if not all, of the Environmental Labeling Programs, were here called Materiais Parcialmente Favoráveis à Sustentabilidade (MPFS – Sustainability Partially Favoring Materials), as they contribute to a greater environmental awareness than other conventional materials. The results of the semi-structured interviews showed that the salespeople, in general, indicated a lack of MPFS, even when those materials were available in the store (detected through on-site observation), indicating a lack of knowledge by the sellers. The application of questionnaires to interior professionals confirmed the results of the interviews, demonstrating an unsatisfactory offer of these materials on the market, in addition to their low disclosure and insufficient technical knowledge by the sellers of the evaluated stores. It was also observed that the majority of respondents indicated that sustainability is important for the planet, however, they attributed a lesser importance when asked about the concerns of the area itself, and a lower level of the use of MPFS in their projects. The analysis of the interrelation between the variables, carried out through Spearman's correlation, allowed to identify that the application of MPFS had a significant association with familiarity of sustainability concepts, importance attributed to the concepts, the application of the concepts in projects, the amount of information requested and the amount of information available about the materials.